Power and Time Dependent Microwave Assisted Fabrication of Silver Nanoparticles Decorated Cotton (SNDC) Fibers for Bacterial Decontamination - Bhardwaj, Abhishek K.; Shukla, Abhishek; Mishra, Rohit K.; Singh, S. C.; Mishra, Vani; Uttam, K. N.; Singh, Mohan P.; Sharma, Shivesh; Gopal, R. (Frontiers in Microbiology, 2017)
Plasmonic nanoparticles (NPs) such as silver and gold have fascinating optical properties due to their enhanced optical sensitivity at a wavelength corresponding to their surface plasmon resonance (SPR) absorption. Present work deals with the fabrication of silver nanoparticles decorated cotton (SNDC) fibers as a cheap and efficient point of contact disinfectant. SNDC fibers were fabricated by a simple microwave assisted route. The microwave power and irradiation time were controlled to optimize size and density of silver nanoparticles (SNPs) on textile fibers. As prepared cotton fabric was characterized for ATR-FTIR, UV-VIS diffuse reflectance, SEM and TEM investigations. Size of SNPs as well as total density of silver atoms on fabric gets increased with the increase of microwave power from 100 W to 600 W. The antibacterial efficacy of SNPs extracted from SNDC fibers was found to be more effective against Gram-negative bacteria than Gram-positive bacteria with MIC 38.5±0.93 µg/mL against Salmonella typhimurium MTCC-98 and 125±2.12 µg/mL against Staphylococcus aureus MTCC-737, a linear correlation coefficient with R2 ranging from ~0.928-0.935 was also observed. About ˃50% death cells were observed through Propidium Iodide (PI) internalization after treatment of SNPs extracted from SNDC fibers with concentration 31.25 µg/mL¬¬¬¬¬. Generation of ROS and free radical has also been observed which leads to cell death. Excellent E. coli deactivation efficacy suggested that SNDC fibers could be used as potentially safe disinfectants for cleaning of medical equipment, hand, wound, water and preservation of food and beverages.